2019
DOI: 10.1038/s41467-019-09506-1
|View full text |Cite
|
Sign up to set email alerts
|

The rise in ocean plastics evidenced from a 60-year time series

Abstract: Plastic production has increased exponentially since its use became widespread in the 1950s. This has led to increased concern as plastics have become prevalent in the oceanic environment, and evidence of their impacts on marine organisms and human health has been highlighted. Despite their prevalence, very few long-term (>40 years) records of the distribution and temporal trends of plastics in the world’s oceans exist. Here we present a new time series, from 1957 to 2016 and covering over 6.5 million nautical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
153
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(154 citation statements)
references
References 26 publications
0
153
0
1
Order By: Relevance
“…Trawling the water's surface with 333 µm mesh nets, Moore et al () reported the mass of microplastic in samples from the North Pacific gyre was six times that of coincident plankton. Although this galvanized global discussion of marine debris, reports existed as early as 1965 (Ostle et al, ). Due to their size, bathymetry, and position in the hydrological cycle, oceans serve as a sink for plastic debris and other persistent pollutants.…”
Section: Fate Of Microplastics In the Oceanmentioning
confidence: 99%
“…Trawling the water's surface with 333 µm mesh nets, Moore et al () reported the mass of microplastic in samples from the North Pacific gyre was six times that of coincident plankton. Although this galvanized global discussion of marine debris, reports existed as early as 1965 (Ostle et al, ). Due to their size, bathymetry, and position in the hydrological cycle, oceans serve as a sink for plastic debris and other persistent pollutants.…”
Section: Fate Of Microplastics In the Oceanmentioning
confidence: 99%
“…Nevertheless, there is a large mismatch between the estimates of the amount of municipal solid plastic waste generated on land that enters coastal waters (5-12 million tonnes yr −1 , Jambeck et al 2015) and the total amount of plastic floating at sea (less than 0.3 million tonnes, Cózar et al 2014, Eriksen et al 2014, van Sebille et al 2015b. Also, there is a discussion about whether the amount of plastics measured at sea over the last few decades , Ostle et al 2019 has kept pace with the growth in global plastic production (Goldstein et al 2012, Geyer et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…MPs are considered an emerging pollutant 3 because they have strong abilities to become enriched in heavy metals 4,5 and persistent organic pollutants (POPs) 6,7 and can affect the growth of organisms 8 . Since 2013, extensive data have been accumulated on the spatial distribution of MPs in coastal areas 9,10 , oceans 11,12 , rivers 13,14 , lakes 15,16 , sediments 17,18 and soil 19,20 . MPs have been found in remote areas 21,22 , which confirmed that MPs could be transported over long distances via the atmosphere 21 and ocean currents 12,15 , which makes MPs an extensive global pollutant.…”
mentioning
confidence: 99%